2013
DOI: 10.1128/aac.02347-12
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Evaluation of the Interaction between Hepatitis C Virus Protease Inhibitor Boceprevir and 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Inhibitors Atorvastatin and Pravastatin

Abstract: bBoceprevir is a potent orally administered inhibitor of hepatitis C virus and a strong, reversible inhibitor of CYP3A4, the primary metabolic pathway for many 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors. Thus, the aim of the present study was to investigate drug-drug interactions between atorvastatin or pravastatin and boceprevir. We conducted a single-center, open-label, fixed-sequence, one-way-crossover study with 20 healthy adult volunteers. Subjects received single-dose atorvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
2
19
2
Order By: Relevance
“…Therefore, the potential of BOC to inhibit atorvastatin gut metabolism might be an additional contributing factor to the increased systemic exposure of atorvastatin. Also consistent with its moderate inhibitory effect on OATP1B1, BOC has been shown to increase the AUC and C max of pravastatin (40 mg) 1.6-and 1.5-fold, respectively (Hulskotte et al, 2011). In humans, pravastatin is eliminated via hepatobiliary and renal excretion mediated by hepatic OATP/MRP2 and renal OAT3, respectively, with minimal metabolism .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, the potential of BOC to inhibit atorvastatin gut metabolism might be an additional contributing factor to the increased systemic exposure of atorvastatin. Also consistent with its moderate inhibitory effect on OATP1B1, BOC has been shown to increase the AUC and C max of pravastatin (40 mg) 1.6-and 1.5-fold, respectively (Hulskotte et al, 2011). In humans, pravastatin is eliminated via hepatobiliary and renal excretion mediated by hepatic OATP/MRP2 and renal OAT3, respectively, with minimal metabolism .…”
Section: Discussionmentioning
confidence: 69%
“…This finding suggests that BOC should have lesser impact (versus rifampin) on the hepatic elimination of atorvastatin and other dual substrates of OATP1B/CYP3A where uptake is the rate-determining step. Indeed, a recent clinical DDI study showed that BOC increased plasma atorvastatin AUC and C max 2.3-and 2.7-fold, respectively (Hulskotte et al, 2011). It is noteworthy that atorvastatin has low intestinal availability [Fa*fg (intestinal availability) = 0.24] (Shitara, 2011) in humans, conceivably due to gut CYP3A4 metabolism and Pgp efflux (Hochman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Boceprevirmay increase the toxicity of statins via inhibition of OATP1B1 decreasing their hepatic uptake and Simeprevir concentrations may be increased when co-administered with the immunosuppressant cyclosporine due to interaction via transporters. [33,[41][42][43] Because grazoprevir is a substrate of OATP1B1/3, its plasma concentration may be significantly increased by OATP1B1/3 inhibitors (e.g., cyclosporine, lopinavir, saquinavir), and its concurrent use is contraindicated.…”
Section: Pharmacologic Basis Of Direct Acting Antiviral Drug Interactionmentioning
confidence: 99%
“…and C max GMR for the comparison of atorvastatin plus boceprevir vs. atorvastatin alone indicate a 2.3-and 2.7-fold increase, respectively ( Table 2) [45]. Boceprevir exposure was unchanged when coadministered with atorvastatin, with GMRs of 1.04 and 0.96 for boceprevir C max and AUC 8 (Table 3) [45]. The increased C max and AUC of atorvastatin are consistent with increases in atorvastatin exposure seen with other inhibitors of CYP3A4 metabolism, such as erythromycin and itraconazole [46].…”
Section: Atorvastatinmentioning
confidence: 91%
“…The AUC ? and C max GMR for the comparison of atorvastatin plus boceprevir vs. atorvastatin alone indicate a 2.3-and 2.7-fold increase, respectively ( Table 2) [45]. Boceprevir exposure was unchanged when coadministered with atorvastatin, with GMRs of 1.04 and 0.96 for boceprevir C max and AUC 8 (Table 3) [45].…”
Section: Atorvastatinmentioning
confidence: 92%